ЛЕГОЧНАЯ АРТЕРИАЛЬНАЯ ГИПЕРТЕНЗИЯ КАК ПРОЯВЛЕНИЕ ПАРАНЕОПЛАСТИЧЕСКОГО СИНДРОМА ПРИ ГИПЕРНЕФР МЕ - А. В. Ягода; И. Б. Павлова; Н. Н. Гладких; Ф. С. Семенова; Ю. В. Громова (Архивъ внутренней медицины)
We give a case report of idiopathic pulmonary arterial hypertension (PAH) in a male patient with cancer of kidney. The hypothesis of pathogenetic link between these diseases was made. The cause of pulmonary hypertension could be cancer with ectopic production  of biologic active substances, growth factors in combination with the susceptibility to develop PAH in poor gene penetrance.